Airport slots and the internalization of congestion by airlines: An empirical model of integrated flight disruption management in Brazil. (October 2018) - Miranda, Victor A.P.; Oliveira, Alessandro V.M.
Abstract: This paper examines the relationship between the control of airport slots by major airlines and their incentives to engage in service quality. We investigate a set of airline strategies regarding possible practices of slot hoarding and slot concentration through mergers aiming at erecting airport barriers to entry. We develop an econometric model of flight disruptions by allowing an integrated management of flight delays, cancellations, aircraft size, price and passengers per flight. We consider the case of the domestic airline industry in Brazil. We find evidence of the internalization of congestion externalities by dominant carriers. We also have some evidence of schedule padding, a strategic trade-off between delays and cancelations, and slot hoarding following a merger. Our results suggest that carriers intensify the internalization of congestion externalities when slot flight concentration increases.